Effect of Vortex Generators on Airfoil NACA 632-415 to Aerodynamic Characteristics Using CFD - Permatasari, Rosyida; Widyawati, Gusty (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2023)
To determine the aircraft’s flight performance, the airfoil type must be considered when designing the wing. A vortex can form when the airfoil travels through a fluid stream with a difference in velocity and pressure around it. Airfoil modification is carried out to delay the occurrence of flow separation by adding a vortex generator. This paper discusses how adding the vortex generator helps slow the stall’s onset and how the vortex generator affects the fluid flow and aerodynamic forces acting on the NACA 632-415. The vortex generator profile is positioned at an x/c = 20% of the chord line’s direction from the leading edge. The variation used is an airfoil’s angle of attack (α). Some parameters to be evaluated include the coefficient lift force (CL), the coefficient drag force (CD), and the gliding ratio (CL/CD). The research was conducted by the CFD method based on the angle of attack that produces the coefficient lift and drag forces. The addition of the vortex generator can delay the flow separation, increase the lift force coefficient by about 24.9%, the drag force coefficient by about 2.7%, and the gliding ratio by 9.1%.